STUDIES ON CARCASS CHARACTERISTICS AND CUT UP YIELDS OF BACKYARD CHICKEN VARIETIES - DHIRENDRA BHONSLE; S. K. CHOURASIA; S.P. INGOLE; MOHAN SINGH; RUPAL PATHAK (The Bioscan, 2019)
The present investigation was carried out to study carcass characteristics and cut up yields in backyard varieties of chicken. Six different varieties namely CARI Shyama, Vanaraja, Kalinga Brown, Black Rock, Caribro Dhanraja and Kuroiler used in Chhattisgarh for backyard poultry were studied. The overall mean dressing percentage were recorded as 77.48 ± 1.19, 79.27 ± 1.13, 79.12 ± 0.58, 79.23 ± 0.5 and 79.90 ± 0.59 per cent for CARI Shyama, Vanaraja, Kalinga Brown, Black Rock, Caribro Dhanraja and Kuroiler, respectively. The overall mean values observed for giblet weight percentage were 4.92 ± 0.01, 4.97 ± 0.10, 5.65 ± 0.20, 5.08 ± 0.06, 4.96 ± 0.11 and 4.89 ± 0.16 % for aforesaid varieties respectively. Breast weight percentage was found to be significantly higher in females compared to males of same age group (P<0.05). However, other carcass traits were not affected by sex of the birds. The proportion of bled weight, dressed weight, leg weight, breast weight and blood loss were significantly (P<0.05) influenced by age of the poultry birds. The results indicated that certain carcass traits of improved varieties of backyard chickens are affected by variety, sex and age of the birds.